PEMIDANAAN TINDAK PIDANA PENCABULAN DAN PERSETUBUHAN DENGAN KEKERASAN OLEH AYAH KANDUNG (PUTUSAN NO.113/PID.SUS/2021/PN.KPG): Sentencing In Sexual Abuse And Forced Intercourse Crimes By A Biological Father (Verdict No.113/Pid.Sus/2021/Pn.Kpg) - Shakira Belva Adara; Maria Silvya E. Wangga (Reformasi Hukum Trisakti, 2025)
Children are a blessing that must be protected, yet they often become victims of abuse by their own parents. This study analyzes the legal protection for victims of sexual abuse and forced intercourse by biological fathers under Law No. 17 of 2016 and the sentencing of perpetrators in Verdict No.113/Pid.Sus/2021/Pn.Kpg. The research method used is descriptive-analytical. The findings result and conclusion indicate that the verdict does not provide detailed legal protection for victims, leading to legal uncertainty and the absence of restitution. The sentencing in this case falls under concursus idealis, where the perpetrator repeatedly committed sexual abuse. The stelsel absorpsi system was applied, with the judge imposing the maximum sentence of 10 years under Article 81(3) of the Child Protection Law.